Traumatic Spinal Cord Injury—Repair and Regeneration. Issue 3 (21st February 2017) - Ahuja, Christopher S.; Nori, Satoshi; Tetreault, Lindsay; Wilson, Jefferson; Kwon, Brian; Harrop, James; Choi, David; Fehlings, Michael G.
Abstract: BACKGROUND: Traumatic spinal cord injuries (SCI) have devastating consequences for the physical, financial, and psychosocial well-being of patients and their caregivers. Expediently delivering interventions during the early postinjury period can have a tremendous impact on long-term functional recovery. PATHOPHYSIOLOGY: This is largely due to the unique pathophysiology of SCI where the initial traumatic insult (primary injury) is followed by a progressive secondary injury cascade characterized by ischemia, proapoptotic signaling, and peripheral inflammatory cell infiltration. Over the subsequent hours, release of proinflammatory cytokines and cytotoxic debris (DNA, ATP, reactive oxygen species) cyclically adds to the harsh postinjury microenvironment. As the lesions mature into the chronic phase, regeneration is severely impeded by the development of an astroglial-fibrous scar surrounding coalesced cystic cavities. Addressing these challenges forms the basis of current and upcoming treatments for SCI. MANAGEMENT: This paper discusses the evidence-based management of a patient with SCI while emphasizing the importance of early definitive care. Key neuroprotective therapies are summarized including surgical decompression, methylprednisolone, and blood pressure augmentation. We then review exciting neuroprotective interventions on the cusp of translation such as Riluzole, Minocycline, magnesium, therapeutic hypothermia, and CSF drainage. We also explore the most promising neuroregenerative strategies in trial today including Cethrin™, anti-NOGO antibody, cell-based approaches, and bioengineered biomaterials. Each section provides a working knowledge of the key preclinical and patient trials relevant to clinicians while highlighting the pathophysiologic rationale for the therapies. CONCLUSION: We conclude with our perspectives on the future of treatment and research in this rapidly evolving field.